Joint Prevalence of Influenza Preventive Behaviors Among Adults-United States, 2020 - Bryant J. Webber; Anne G. Wheaton; Peng-jun Lu; Geoffrey P. Whitfield (SAGE Publishing, 2023)
Introduction/Objectives: The Centers for Disease Control and Prevention recognizes routine vaccination, sufficient sleep, and adequate physical activity as behavioral approaches to reduce the incidence of influenza. We aimed to determine the joint national prevalence of these health behaviors among U.S. adults, which has not been reported. Methods: We used the 2020 National Health Interview Survey to assess prevalence of receiving influenza vaccination in the past 12 months, obtaining sufficient sleep, and achieving adequate physical activity among U.S. adults (n = 30,312). We calculated the joint prevalence overall and by sociodemographic and health-related variables. Results and Conclusions: The overall joint prevalence was 8.5% (95% CI, 8.0-9.0). Prevalence was lower among older persons (vs younger); Hispanic and non-Hispanic Black persons (vs non-Hispanic White); current and former smokers (vs never smokers); postpartum women (vs neither pregnant nor postpartum); and those with a history of coronary heart disease, hypertension, stroke, diabetes, and chronic obstructive pulmonary disease (vs not having those respective condition). In addition to recommending annual vaccination, primary care providers might encourage sufficient sleep and adequate physical activity-especially among patients who have increased risk for influenza complications and are less likely to achieve these behaviors.